“Análisis de eficiencia energética en el sistema eléctrico del Servicio Ecuatoriano de Capacitación Profesional SECAP-Ambato’’. - Corrales Tapia, Carlos Ramiro (2022)
In recent years, a series of initiatives have been developed aimed at improving the use of electrical energy in the Ecuadorian Professional Training Service SECAP. One of the lines of work, developed in collaboration with the Instituto Superior Tecnológico Tungurahua, is oriented towards the integration of measures in favor of energy consumption in the building and laboratories, thus reducing the energy rate. Based on this study, the objective of this project is to present proposals in a practical way to reduce electrical energy consumption by applying knowledge of efficiency and technical considerations to establish optimal energy savings. Subsequently, a technical analysis was carried out with the use of specialized measurement equipment to observe the behavior of the loads and electrical consumption of the laboratories and building, taking as a fundamental point the study of the power factor, tariff specifications and energy efficiency proposals to obtain better payroll performance. Finally, technical and economic improvements will be generated that allow reducing energy consumption as well as regulating factors that allow regulation in the electrical system.